KAJIAN MORFOMETRI DAN MOLEKULER IKAN SELAR MATA BESAR DAN SELAR MATA KECIL YANG DI DARATKAN DI PELABUHAN PERIKANAN SAMUDERA BITUNG - Rudi Saranga; Heru Santoso; Nova Tumanduk; Hetty Ondang; Jul Manohas (JURNAL BLUEFIN FISHERIES, 2019)
Abstract–Bigeye scad resources which landed at Bitung Oceanic Fishing Port is one of important fish capture in Bitung because its have economic value and second ratings after scad mackerel in product volume. Bigeye scad fish capture was often mixed with another species in fisherman fish capture, so it making difficult to distinguish clearly.The objective of this research are : 1) to indentification bigeye scad in morfology, 2) to analyzemolecular bigeye scad, (3) to evidence the bigeye scad are the same species or not.Sample for the study were collectedfish landing site at Bitung Ocean Fishing Port from December 2015 to March 2016. The methodology of the research is survey research. For data analysis using truss morfometrics, principal component analysis (PCA) and mtDNA region COI. The result of this research indicated that based on the analysis of morphometric characters and PCA, bigeye scad and smalleye scad have differences in morphology, but result of mt DNA-COI analysis indicated those species are the same as Selar crumenophthalmus with similarity value 99,67%. Keywords: bigeye scad, morfometric, mtDNA-COI